2007
DOI: 10.1007/s00296-007-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular dysfunction in rheumatoid arthritis assessed by laser Doppler anemometry: relationship to soluble adhesion molecules and extraarticular manifestations

Abstract: In search of a noninvasive diagnostic test for rheumatoid vasculitis (RV), this study addressed the questions whether changes in capillary blood cell velocity (CBV) detected by laser Doppler anemometry in patients with rheumatoid arthritis (RA) were correlated with the levels of soluble adhesion molecules and whether cutaneous flow abnormalities may reflect extraarticular manifestations in RA. In 31 RA patients and 20 patients with osteoarthritis (OA), CBV was measured in the skin above the left ring finger at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, Meyer et al showed modifications of the normal blood flow velocity and microvascular dysfunction in RA [20]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Meyer et al showed modifications of the normal blood flow velocity and microvascular dysfunction in RA [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Others have identified unique expression profiles in RA patients [48,49,50], although ICAM-1 and P-selectin were also found to be elevated in RA patients in these studies. Several investigators have failed to demonstrate differences in adhesion molecule expression between patients and healthy controls [51]. There is also discordance with regard to the correlation between adhesion molecule expression and markers of disease activity.…”
Section: Clinical Findings Of Major Chronic Inflammatory Diseases mentioning
confidence: 99%
“…In an older study, functional impairment of the capillary wall was detected after the intravenous injection of fluorescein sodium using dynamic fluorescence nailfold NVC in patients with RA [ 40 ]. Other microvascular alterations in normal bloodstream have been described in RA patients, including reduced reactive hyperemia in cutaneous capillaries compared to patients with osteoarthritis [ 41 ]. Reduced capillary blood flow and cold-induced vasospasm have been additionally observed using nailfold NVC combined with a cold provocation test [ 42 ].…”
Section: Abnormal Nvc Findings In Patients With Ramentioning
confidence: 99%